The effects of liberalization and deregulation on the performance of financial institutions: The case of the German life insurance market - Lucinda Trigo Gamarra (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
The German insurance market was liberalized in 1994 by the introduction of the 'single passport' allowing European insurers to operate throughout the entire European Union. The European directive put also an end to price and insurance contract terms regulation. These measures were meant for removing the obstacles to competition within and between the insurance markets of the member states aiming at an increased efficiency of the European insurance markets. We analyze to which extent this aim has been achieved in the German life insurance market. The development of market performance is measured by changes in technical cost and profit efficiency levels since the liberalization, as well as a measurement of technological change. Technical cost efficiency levels are estimated by applying a stochastic 'true' fixed effects distance frontier (Greene, 2005). Non-standard profit efficiency is derived in a second step following Kumbakhar (2006). According to our results, the industry experienced positive total factor productivity (TFP) growth during the observation period, which is mainly driven by substantial positive technological change. Technical cost efficiency and profit efficiency remained stable on average, but significant positive scale efficiency change can be found indicating that market consolidation in the presence of increasing returns to scale led to efficiency gains of the firms.
Keywords: D24; G22; G28; 330; Insurance markets; Total factor productivity growth; Stochastic Frontier Analysis; Lebensversicherung; Versicherungsmarkt; Deregulierung; EU-Binnenmarkt; Wirkungsanalyse; Technische Effiz